Prevalence of Refractive Errors in School Children Aged 11-15 Years in Jalalabad city of Nangarhar Province, Afghanistan – a cross-sectional Study - , Assistant Professor Dr. Mohammad Haris Abdianwall; Associate Professor Dr. Gholam Farooq (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
Introduction: the purpose of the study was to estimate the prevalence and types of uncorrected refractive errors (URE) among school-going children aged 11-15 years in Jalalabad City of Nangarhar Province. Methodology: the study was population-based descriptive cross-sectional in design, conducted between 01-September-2007 and 10-October-2007 in schools of Jalalabad City. The sample size was calculated as 1034 and a two-stage cluster sampling method was used for data collection. In the first stage, 4 schools were selected and in the second, classes were randomly selected. A structured, pretested and self-prepared questionnaire was used for data collection. Visual acuity (VA) of the students was recorded using Snellen’s test type in the daylight and each eye was examined separately. Students with VA less than 6/12 were examined and non-cycloplegic refraction was performed using auto-refractometer for types of refraction. Data were analyzed using Epi-info, descriptive statistics of the variables were presented by giving number and percent using table and chart. Result: The sample size was 1034, we invited 960 students (580 males and 380 females), 951 (92.0%) students participated in the study. The prevalence of URE was found out as 5.5% (95% CI, 4.1% - 7.2%). In male students, the prevalence of URE was discovered as 28 (4.9%) while it was found to be 24 (6.4%) in female students. The prevalence of different types of RE, myopia, hyperopia, and astigmatism was found to be 2.8%, 1.4%, and 0.5% respectively. Conclusion: the prevalence was found to be high among students in Jalalabad City and the single cause of lower VA was URE. Lack of school eye health programs and limited availability or unequal distribution of the eye care services increase this problem. Integration of school eye health in the school health programs and performing mass school screening in rural and urban areas are recommended. Furthermore, for the proper estimation of URE in the whole Nangarhar Province, performing a survey of cycloplegic refraction with a representative sample size was recommended.